PEMBAGIAN BANTUAN SEMBAKO OLEH DOSEN SEKOLAH TINGGI TEOLOGI TABGHA BATAN DAN CAHAYA OBOR BERKAT DI MALL BOTANIA DUA BATAM CENTER - Tony Suhartono; Tahan Sitanggang; Setya Budi (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2023)
After Covid-19 Pandemic impacted almost every aspect of human life both globally and Indonesia, including Batam city. The economic impact of the pandemic has greatly affected Batam residents, as seen from the increasing unemployment rate in the city of Batam and the difficulty in finding work in the city. After the end of the Pandemic, the economy in the city of Batam did not recover immediately, but it needed a process, especially in the economic sector. During difficult times like this, the Cahaya Obor Berkat Foundation distributes food groceries to people in need. Not only basic food assistance, but also other types of assistance, such as the form of health counseling and educational assistance. Tabgha Theological Seminary Lecturers also worked closely with the Cahaya Obor Berkat Foundation to collect basic necessities for food groceries and distribute them to the people in Baloi Village who needed assistance. To obtain data on who is entitled to assistance, the lecturers requested data from the RT/RW in the Baloi Village Complex who needed assistance. As followers of Christ we should live peacefully with others who do not share our values ​​or accept teachings above them. It is based on 1 John 4:19-21 : “We love because he first loved us. Whoever claims to love God yet hates a brother or sister is a liar. For whoever does not love their brother and sister, whom they have seen, cannot love God, whom they have not seen. And he has given us this command: Anyone who loves God must also love their brother and sister.”